2019
DOI: 10.1016/j.chemosphere.2018.10.146
|View full text |Cite
|
Sign up to set email alerts
|

Effect of soil properties on Pb bioavailability and toxicity to the soil invertebrate Enchytraeus crypticus

Abstract: h i g h l i g h t s Pb toxicity to Enchytraeus crypticus was determined in six different natural soils. Soil properties highly affected Pb availability, uptake and toxicity to E. crypticus. CaCl 2 extractable Pb best explained Pb bioaccumulation and toxicity in all soils. pH CaCl2 was main factor predicting Pb toxicity based on total soil concentrations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 45 publications
(21 citation statements)
references
References 29 publications
2
17
1
1
Order By: Relevance
“…This was supported by the strong correlation between the contents of Pb in the plant shoots and the contents of total Pb (r = 0.80, p < 0.001) and extractable Pb (r = 0.81, p < 0.001). This result also implies the strong effect of the bioavailability of Pb in the soil on the uptake and accumulation of Pb in plant shoots, consistent with previous studies [65,82]. Our results also showed higher contents of Pb in the shoots of I. aquatica (586 mg/kg-DW) than those reported (179 and 232 mg/kg) when the plants were growing in soil containing 864 and 3352 mg Pb/kg, respectively [32], possibly because of the differences in the Pb contents in the soil.…”
Section: Bioaccumulation Of the Studied Elements In Plant Speciessupporting
confidence: 92%
See 1 more Smart Citation
“…This was supported by the strong correlation between the contents of Pb in the plant shoots and the contents of total Pb (r = 0.80, p < 0.001) and extractable Pb (r = 0.81, p < 0.001). This result also implies the strong effect of the bioavailability of Pb in the soil on the uptake and accumulation of Pb in plant shoots, consistent with previous studies [65,82]. Our results also showed higher contents of Pb in the shoots of I. aquatica (586 mg/kg-DW) than those reported (179 and 232 mg/kg) when the plants were growing in soil containing 864 and 3352 mg Pb/kg, respectively [32], possibly because of the differences in the Pb contents in the soil.…”
Section: Bioaccumulation Of the Studied Elements In Plant Speciessupporting
confidence: 92%
“…The ratio of the content of extractable Pb to that of total Pb in the present study was lower than that reported by Rodríguez-Seijo et al [63] and Ngoc et al [64], but higher than that reported by Zhang et al [65] and Lenart and Wolny-Koładka [66]. The differences in the proportions of extractable Pb in different studies may be attributable to the total Pb contents in the soils and the different properties of the soils (e.g., soil pH, soil texture, organic carbon content, cation exchange capacity, calcium carbonate equivalents, and nutrient balance) [11,[63][64][65][66][67][68]. Extractants also play an important role in the amounts of extractable metals detected [63,64,69].…”
Section: Contents Of N P K As and Heavy Metals In Soilscontrasting
confidence: 84%
“…The untreated seep soils had soil solution Pb concentrations (all <6 µg/L) that were below or marginally above the estimated typical background levels. One study (Zhang et al 2019) showed that even in a very sensitive soil from Germany the concentration causing just a 10% reduction in the reproduction (i.e., the reproduction EC10) of the Enchytraeus crypticus worm was 6 µg/L, whereas the EC10 values in the other soils tested ranged from 21 to 90 µg/L. This would suggest that the Pb soil solution concentrations in the seep soils would not pose any substantial risk to invertebrates.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, higher significant BCF Pb of stem resulted from 450 and 850 mg Pb acetate/kg soil, without a significant difference between such treatments. Soil properties such as pH, CEC, and Ca concentration have a significant (p ≤ 0.05) effect on the bioavailability of Pb in soil (Zhang et al 2019). BCF and TF are key values that evaluate a plant's potential for phytoextraction or phytoestabilization (Rafati et al 2011).…”
Section: Bioconcentration Factor (Bcf) Translocation Factor (Tf %)mentioning
confidence: 99%